Picture-Based Virtual Touring - Geng, Weidong; Pan, Yunhe; Li, Ming; Yang, Jian (International Journal of Virtual Reality, 2000)
This paper presents an image-based approach for virtual touring which use panoramas and picture-based animation to compose a virtual environment. Two typical touring behaviors, looking around and moving in one direction, are mimicked by players based on realtime image processing engine. This approach has been implemented in VRTOURISM. In addition to panoramic views, the system includes picture-based animation for moving forward to the next scene nodes. The paper describes the architecture, the authoring tools, and the interactive players of the VR system.